The convalidation of marriage in canon law - Bartczak, Adam (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
The convalidation of marriage in canon law is a process where the invalidly contracted marriage becomes validly contracted in the light of law. The author of this article analyses the notion of the convalidation of the marriage, basing on Polish canon law literature and on opinions of different authors. In canon law there are considerable differences between two kinds of the convalidation: convalidatio simplex and sanatio in radice. In Polish literature there exists only one word denoting these two kinds. This institution is of vital importance in canon law, as it has a legal effect on the marriage, which de facto exists in reality.